Fish oil recovery from viscera of Indian mackerel (Rastrelliger kanagurta) by supercritical fluid: an optimization approach - Ferdosh, Sahena; Sarker, Md. Zaidul Islam; Nik Abd Rahman, Nik Norulaini; Selamat, Jinap; Karim, Md. Rezaul; Abdul Razak, Tariq; Abd Kadir, Mohd Omar (Chinese Chemical Society/Zhongguo Huaxuehui, 2012)
Fish viscera, a waste of fish processing industry, can be exploited as a source of PUFA-rich fish oil for use in food or pharmaceutical industry and at the same time the environment can be protected from pollution by fish wastes. Fish oil was recovered from viscera of Indian Mackerel (Rastrelliger kanagurta), by different supercritical fluid extraction (SFE) e.g. continuous, co-solvent, soaking, and pressure swing techniques and the yields were compared with that of the solvent extraction method. The SFE parameters such as pressure, temperature, and CO2 flow rate were optimised by employing Response SurfaceMethodology (RSM) with a view tomaximize the oil yield andminimize CO2consumption. The central composite rotatable design (CCRD) consisting of three variables provided 20 experimental settings.Multiple regressions determined the coefficients of the second-order polynomial equation. The optimum parameters for all 4 techniques applied were found to be 35 MPa, 60 °C, and 2 mL min-1 with an Oil recovery ranging from 93 to 99%. The study demonstrated a lower CO2 consumption by the soaking and pressure swing techniques at the optimized conditions. Thus, the soaking and pressure swing techniques were most effective for extracting oil from fish viscera.